PENGARUH SEKTOR BASIS, MODAL, DAN TENAGA KERJA TERHADAP KONVERGENSI PERTUMBUHAN EKONOMI DI DKI JAKARTA - Zahra, Muthia; Muttaqin, Aminnullah Achmad (Journal of Development Economic and Social Studies, 2023)
Convergence is a process where high economic growth reduces development inequality. Convergence occurs when poorer regions experience higher economic growth than richer regions. DKI Jakarta is a province that has high economic growth, but inequality between cities/regencies in DKI Jakarta from 2000 - 2010 is still high. This study uses the Fixed Effect Model (FEM) to see indications of convergence and the factors that influence it in DKI Jakarta during 2011-2021. The results showed that there was convergence between cities / regencies in DKI Jakarta Province, characterized by a negative and significant initial per capita income coefficient value. The base sector GRDP, capital, and labor variables are proven to be jointly able to influence economic growth and accelerate the half-life of convergence from 72 years to 9 years. Base sector income can significantly accelerate the convergence so that the policy of developing the tertiary sector in the city area; as well as the primary and secondary sectors in Kepulauan Seribu Regency as a base sector can be considered to accelerate convergence.